THE ROLE OF TRADE UNION IN ENSURING PRODUCTIVITY IN AN ORGANIZATION: A CASE OF GENERAL AGRICULTURAL WORKERS UNION (GAWU) IN GHANA - Asiedu-Darko, Emmanuel; Quaye, Saffiatu; Acheampong, Rita (International Journal of Research -GRANTHAALAYAH, 2022)
This work was carried out to assess the role of trade unions in ensuring productivity in an organization The General Agricultural Workers Union (GAWU) of Trade Union Congress in Ghana was considered as the target population of which one hundred members were interviewed. Questionnaires were used to solicit views from unionized employees selected for the study. Five union leaders identified under GAWU were also interviewed through face to face. The research assumed content analysis to evaluate how the union activities involving increasing co-operation and wellbeing among workers, Work for the progress employees, ensure punctuality to work and facilitate job security and reduce pressure. The result revealed that members were not enthused about the union’s role in ensuring punctuality to work, working for progress of employees and facilitating job security and reducing pressure. However members applauded the Union efforts in ensuring increased communication between the employer and the employees. The study suggested that there is a need for the Union to ensure that that workers play their roles as expected of them to ensure productivity in the organization. Workers should be motivated, that putting organizational interest first rather than personal interest is crucial to the sustainability of every organization